N-glycosylated catalytic unit meets O-glycosylated propeptide: complex protein architecture in a fungal hexosaminidase - Plíhal, O; Sklenár, J; Kmonícková, J; Man, P; Pompach, P; Havlícek, V; Kren, V; Bezouska, K (Biochemical Society transactions, 2004)
beta-N-Acetylhexosaminidase from a filamentous fungus Aspergillus oryzae is a secreted enzyme known to be an important component of the binary chitinolytic system. Cloning of the hexA gene and sequencing of the enzyme revealed its unique preproprotein structure. While the enzyme's zincin-like and catalytic domain had significant similarities with members of the glycohydrolase 20 family, the propeptide was unique for the fungal enzyme. Detailed pulse-chase and inhibition studies revealed that propeptide was processed during the biosynthesis of the enzyme. Moreover, the presence of propeptide was necessary for enzyme activation, dimerization and secretion. The catalytic unit was N-glycosylated, and the propeptide was O-glycosylated, both in their C-terminal parts. Deglycosylation experiments revealed that the N-glycosylation increased the stability and solubility of the enzyme. In contrast, O-glycosylated propeptide was necessary to attain the full enzymic activity.
Keywords: Chromatography, Gel; Protein Structure, Tertiary; beta-N-acetylhexosaminidasy; Time Factors; Chitin; koncentrace vodíkových iontů; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; hexosaminidasy; glykosylace; Cloning, Molecular; gelová chromatografie; Hexosaminidase A; Peptides; Glycosylation; Hydrogen-Ion Concentration; chitin; Catalytic Domain; časové faktory; klonování DNA; Hexosaminidases; peptidy; spektrometrie hmotnostní - ionizace laserem za účasti matrice; hexosaminidasa A; beta-N-Acetylhexosaminidases; Aspergillus oryzae; katalytická doména; terciární struktura proteinů